Directed energy missions for planetary defense. Issue 6 (15th September 2016) - Lubin, Philip; Hughes, Gary B.; Eskenazi, Mike; Kosmo, Kelly; Johansson, Isabella E.; Griswold, Janelle; Pryor, Mark; O'Neill, Hugh; Meinhold, Peter; Suen, Jonathan; Riley, Jordan; Zhang, Qicheng; et al.
Abstract: Directed energy for planetary defense is now a viable option and is superior in many ways to other proposed technologies, being able to defend the Earth against all known threats. This paper presents basic ideas behind a directed energy planetary defense system that utilizes laser ablation of an asteroid to impart a deflecting force on the target. A conceptual philosophy called DE-STAR, which stands for Directed Energy System for Targeting of Asteroids and exploration, is an orbiting stand-off system, which has been described in other papers. This paper describes a smaller, stand-on system known as DE-STARLITE as a reduced-scale version of DE-STAR. Both share the same basic heritage of a directed energy array that heats the surface of the target to the point of high surface vapor pressure that causes significant mass ejection thus forming an ejection plume of material from the target that acts as a rocket to deflect the object. This is generally classified as laser ablation. DE-STARLITE uses conventional propellant for launch to LEO and then ion engines to propel the spacecraft from LEO to the near-Earth asteroid (NEA). During laser ablation, the asteroid itself provides the propellant source material; thus a very modest spacecraft can deflect an asteroid much larger than would be possible with a system of similar mission mass using ion beam deflection (IBD) or a gravity tractor. DE-STARLITE is capable of deflecting an Apophis-class (325 m diameter) asteroid with a 1- to 15-year targeting time (laser on time) depending on the system design. The mission fits within the rough mission parameters of the Asteroid Redirect Mission (ARM) program in terms of mass and size. DE-STARLITE also has much greater capability for planetary defense than current proposals and is readily scalable to match the threat. It can deflect all known threats with sufficient warning.